G protein mutations in pituitary tumors: a study on Turkish patients - (:unkn) unknown (My University, 2003)
Activating mutations of the G proteins, Gsalpha (gsp) and Gi2alpha (gip) have been reported in subsets of pituitary tumors. The objective of the study was to assess the frequency of gsp and gip mutations in pituitary tumors from Turkish patients and to investigate the possibility of mutations of protein kinase A catalytic subunit (PKAC) that activates the downstream effectors of adenylyl cyclase. PCR-amplified genomic DNA was analyzed for the presence of mutations in codons 201 and 227 of Gsalpha, codon 179 and 205 of Gi2alpha and codon 196 of PKAC, by single strand conformation polymorphism analysis, allele-specific oligonucleotide hybridization and DNA sequencing. Twenty-two patients from Turkey, 15 females and 7 males were investigated; 7 somatotroph adenomas, 7 clinically non-functioning tumors, 7 prolactinomas and 1 corticotroph adenoma. G protein mutations were identified in 6 of 22 (27.3%) pituitary tumors. Four tumors (3/7 somatotroph adenomas, 43%, 1/7 clinically non-functioning tumor) demonstrated gsp mutations at codon 201 arginine to cysteine and one recurrent somatotroph adenoma demonstrated a mutation of the Gi2alpha gene at codon 193 lysine to arginine. One tumor exhibited a C to T variation in the intervening sequence between codons 179 and 205 of the Gi2alpha gene. No mutations at codon 227 of Gsalpha, codons 179 and 205 of Gi2alpha and codon 196 of the PKAC gene were identified.
Keywords: Adult; Female; Humans; Middle Aged; Turkey; Male; Sequence Analysis, DNA; DNA; Mutation; Alleles; Autoradiography; Reverse Transcriptase Polymerase Chain Reaction; Pituitary Neoplasms; GTP-Binding Protein alpha Subunits, Gs; In Situ Hybridization; Polymorphism, Single-Stranded Conformational; GTP-Binding Proteins; GTP-Binding Protein alpha Subunits, Gi-Go; Mutagenesis; Oligonucleotides